Cardiac resynchronization therapy pacemaker: critical appraisal of the adaptive CRT-P device [Corrigendum] - Daoud GE (Dove Medical Press, 2016)
On page 21, Figure 1, Intrinsic AV ≥200 ms should have been Intrinsic AV ≤200 ms.Read the original article.